Preparação, caracterização e aplicação de eletrodos tridimensionais de carbono vítreo reticulado recobertos com filmes de PbO2 para a degradação do corante reativo AR 19 e glifosato - Farinos, Rosimeire Martins (Universidade Federal de São Carlos, 2016)
Electrodeposition of a PbO2 film was performed onto reticulated vitreous carbon (RVC) substrates with porosities of 45, 60, and 80 ppi, at 65 ºC in a flow reactor, starting with a solution containing Pb(NO3)2, surfactant, and HNO3. Investigation was made of the effects of current density and electrodeposition time on the coverage and uniformity of the PbO2 film formed. The electrodes were characterized using scanning electron microscopy, X-ray diffractometry, and linear potential scanning. The use of high currents resulted in the formation of thick films in regions close to the counter-electrode, which compromised film adhesion, while the application of lower currents ensured a uniform and adherent PbO2 coating. In tests of the decoloration of AR 19 dye using the best electrodes produced, better performance was achieved using RVC/PbO2, compared to VC/PbO2, due to the greater specific surface area and increased hydrodynamic turbulence caused by the tridimensional substrate, which increased the mass transport coefficient and therefore enhanced the degradation process. The optimum conditions for use of the RVC/PbO2 electrode were 3.5 mA cm-2 and 30 minutes of electrosynthesis. Electrochemical degradation of the herbicide was performed using the 60 ppi RVC/PbO2 electrode in a flow reactor. Box-Behnken design was used to study the effects of current density, flow, and temperature on the kinetics of degradation (COD) and mineralization (TOC), current efficiency (ε), and energy consumption (η). The best degradation and mineralization kinetics values were obtained with the upper limits of the variables studied (30 mA cm-2, 150 mL min-1, and 50 oC). Increasing the flow rate from 150 to 1500 mL min-1 increased εG from 18% to 65%, and decreased ηG from 72 to 33 kWh kg-1, reflecting a higher mass transport coefficient. In comparative tests, using degradation of the herbicide and phenol, the performance of the RVC/PbO2 electrode was slightly lower than that of a boron-doped diamond (BDD) electrode. Considering that the RVC/PbO2 device is less expensive than DDB electrodes, it can be concluded that this tridimensional electrode is promising for use in the degradation of organic pollutants.
Preparation, characterization and application of threedimensional reticulated vitreous carbon electrodes coated with Pbo2 films for degradation of effluents containing dye reactive AR19 e glyphosate
Keywords: Composto orgânico; Degradação; Chumbo; Tridimensional; Reatores; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA